Effect of cold ambient temperature on heat flux, skin temperature, and thermal sensation at different body parts in elite biathletes - Blokker, Thomas; Bucher, Elias; Steiner, Thomas; Wehrlin, Jon Peter (Frontiers in Sports and Active Living, 2022)
Introduction When exercising in the cold, optimizing thermoregulation is essential to maintain performance. However, no study has investigated thermal parameters with wearable-based measurements in a field setting among elite Nordic skiers. Therefore, this study aimed to assess the thermal response and sensation measured at different body parts during exercise in a cold environment in biathletes. Methods Thirteen Swiss national team biathletes (6 females, 7 males) performed two skiing bouts in the skating technique on two consecutive days (ambient temperature: −3.74 ± 2.32 °C) at 78 ± 4% of maximal heart rate. Heat flux (HF), core (Tcore) and skin (Tskin) temperature were measured with sensors placed on the thigh, back, anterior and lateral thorax. Thermal sensation (TS) was assessed three times for different body parts: in protective winter clothing, in a race suit before (PRE) and after exercise (POST). Results HF demonstrated differences (p < 0.001) between sensor locations, with the thigh showing the highest heat loss (344 ± 37 kJ/m2), followed by the back (269 ± 6 kJ/m2), the lateral thorax (220 ± 47 kJ/m2), and the anterior thorax (192 ± 37 kJ/m2). Tcore increased (p < 0.001). Tskin decreased for all body parts (p < 0.001). Thigh Tskin decreased more than for other body parts (p < 0.001). From PRE to POST, TS of the hands decreased (p < 0.01). Conclusion Biathletes skiing in a race suit at moderate intensity experience significant heat loss and a large drop in Tskin, particularly at the quadriceps muscle. To support the optimal functioning of working muscles, body-part dependent differences in the thermal response should be considered for clothing strategy and for race suit design.